Pengaruh Total Aset Turnover (Tato) Dan Return On Equity(Roe) Terhadap Pertumbuhan Laba (Studi Kasus Pada Perusahaan Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Selama Masa Pandemi Covid -19) - Ira Rahmawati; Dini Verdania Latif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
During the Covid-19 pandemic, the pharmaceutical industry faced a condition where the demand for pharmaceutical products related to the handling of Covid-19 experienced a significant increase, but was not in line with other products that were not directly related to the handling of Covid-19. So to know the success or failure of the company's performance can be seen in the financial statements. The objects in this study are Total Asset Turnover (TATO), Return On Equity (ROE), and Profit Growth with research samples of 11 (eleven) BUMN companies in the pharmaceutical sector from 2019-2021 during the covid pandemic including PT. Pyridam Farma Tbk, PT. Organon Pharma Indonesia Tbk, PT. Tempo Scan Pasifik Tbk, PT. Kimia Farma (Persero) Tbk, PT. Herbal Medicine and Pharmaceutical Industry Sido Muncul Tbk, PT Indofarma (Persero) Tbk, PT. Soho Global Health Tbk, PT. Kalbe Farma Tbk, PT. Merck Tbk, PT. Darya Varia Laboratoria Tbk, and PT. Pharos Tbk. Data is processed using SPSS 25, including Descriptive Test, Classical Assumption Test, Multiple Linear Regression Analysis and Hypothesis Testing using T Test, F Test and Coefficient of Determination Test. The results of the study prove that the variables Total Asset Turnover (TATO) and Return On Equity (ROE) have a positive and significant influence on profit growth. Keywords: Total Asset Turnover (TATO), Return On Equity (ROE), Profit Growth